Evodiamine Attenuates Experimental Colitis Injury Via Activating Autophagy and Inhibiting NLRP3 Inflammasome Assembly - Ding, Wenwen; Ding, Zhiquan; Wang, Yong; Zhu, Yan; Gao, Qi; Cao, Wangsen; Du, Ronghui (Frontiers in Pharmacology, 2020)
Autophagy and NLRP3 inflammasome were associated with the process of colitis. Drugs targeting NLRP3 inflammasome and autophagy to treat colitis are absent, and they are urgently required. Herein, we examine the effect of evodiamine, extracted from the fruit of Evodiae Fructus, on experimental colitis induced by DSS and exposit whether evodiamine effects on autophagy and NLRP3 inflammasome. Our data indicated that colitis was ameliorated by evodiamine, including the improvement of mice body weight, colon length, histopathologic score, and the disease activity index. We also observed that evodiamine restrained the formation of the NLRP3 inflammasome by inhibiting the ASC oligomerization and caspase-1 activity in THP-1 macrophages. Our results demonstrated evodiamine inhibit NLRP3 inflammasome activation via the induction of autophagosome-mediated degradation of inflammasome and the inhibition of NFκB pathway, which synergistically contribute to the effect of evodiamine in colitis. It indicates the potential use of evodiamine in inflammatory bowel diseases treatment.